Purification and characterization of a novel nucleoside phosphorylase from a Klebsiella sp. and its use in the enzymatic production of adenine arabinoside. - Ling, F (1990)
An adenosine-assimilating bacterium, Klebsiella sp. strain LF1202, inducibly formed a novel nucleoside phosphorylase which acted on both purine and pyrimidine nucleosides when the cells were cultured in medium containing adenosine as a sole source of carbon and nitrogen. The enzyme was purified (approximately 83-fold, with a 17% activity yield) to the homogeneous state by polyacrylamide gel electrophoresis. The molecular weight of the purified enzyme was calculated to be 125,000 by gel filtration of Sephadex G-200 column chromatography, although the enzyme migrated as a single protein band with a molecular weight of 25,000 on sodium dodecyl sulfate (SDS)-polyacrylamide gel electrophoresis; thus, it was thought to consist of five identical subunits. Besides purine nucleosides (adenosine, inosine, and guanosine), the purified enzyme also acted on pyrimidine nucleosides such as uridine, 2'-deoxyuridine, and thymidine. The purified enzyme catalyzed the synthesis of adenine arabinoside, a selective antiviral pharmaceutic agent, from uridine arabinoside and adenine.